2014
DOI: 10.1136/oemed-2014-102427
|View full text |Cite
|
Sign up to set email alerts
|

Change in psychological distress following change in workplace social capital: results from the panel surveys of the J-HOPE study

Abstract: Boosting workplace social capital may promote mental health in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…Previous prospective studies from Finland have investigated the link between workplace social capital and health and found that low individual-level workplace social capital was associated with depression,12 13 hypertension (only among men)14 and all-cause mortality,15 but found no associations with work-unit social capital. Further, a prospective Japanese study found that increased workplace social capital was associated with decreased mental distress 1. Another recent Japanese study replicated the findings of Kouvonen  et al 12 and reported that high workplace social capital was a protective factor against the onset of major depressive episodes 16…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous prospective studies from Finland have investigated the link between workplace social capital and health and found that low individual-level workplace social capital was associated with depression,12 13 hypertension (only among men)14 and all-cause mortality,15 but found no associations with work-unit social capital. Further, a prospective Japanese study found that increased workplace social capital was associated with decreased mental distress 1. Another recent Japanese study replicated the findings of Kouvonen  et al 12 and reported that high workplace social capital was a protective factor against the onset of major depressive episodes 16…”
Section: Introductionmentioning
confidence: 77%
“…There is an increasing interest in identifying resources at workplaces that may help preserve the health and well-being of the employees 1. The concept of social capital could be relevant in this regard, as it refers to features of social organisations including formal and informal networks, participation, reciprocity and interpersonal trust, which facilitate coordination, collaboration and collective action for mutual benefit 2–4.…”
Section: Introductionmentioning
confidence: 99%
“…The scale score was found to correlate positively with supervisors’ support (r=0.409, p<0.01), coworker support (r=0.459, p<0.01) and collective efficacy (r=0.518, p<0.01), suggesting its convergent validity 21. While the J-HOPE study asked six questions on WSC and all these questions were used to measure WSC in a previous study using the data,9 23 only the three-item scale was fully tested for its reliability and validity until now 22. Respondents were grouped into tertiles (high, middle and low) of WSC.…”
Section: Methodsmentioning
confidence: 94%
“…The J-HOPE study was conducted in 12 companies 9. However, we used data from one of these companies where the onset of MDE was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Prospective studies have shown that low (self-reported) individual-level ratings of organizational social capital is associated with higher levels of self-reported depression [39], while low organizational social capital at both the individual and work unit level is associated with higher risks of poor health [40]. A 1-year follow-up study furthermore found that increased workplace social capital was associated with lower levels of psychological distress [41].…”
Section: Introductionmentioning
confidence: 94%